DISKUSI PUBLIK PENCEGAHAN DAN PENANGANAN TPPO BERBASIS MASYARAKAT SERTA PENERAPAN UNDANG-UNDANG KESEJAHTERAAN IBU DAN ANAK DI PROVINSI SUMATERA SELATAN - Badarudin Azarkasyi (Karya : Jurnal Pengabdian Masyarakat, 2024)
Abstract Serious crimes that have an impact on the security, human rights, and social welfare of the community. South Sumatra Province, like other regions, faces significant challenges in providing in-depth information on the dangers of trafficking, the modus operandi that perpetrators often use, and the rights regulated in the Maternal and Child Welfare Law are a big task together. Community service method and Focus Group Discussion (FGD): Holding interactive discussions with specific community groups to explore their understanding of human trafficking crimes and maternal and child welfare, as well as finding solutions together. This activity resulted in several important achievements, including Increased Public Awareness: There is an increase in awareness among the people of South Sumatra about trafficking and its negative impacts, especially on vulnerable groups such as mothers and children. This is shown by the increasing number of reports of suspected human trafficking from the community to the authorities after the activities took place. Involving non-governmental organizations (NGOs) and the government in counseling campaigns. For example, holding meetings with the community and providing information that can be accessed by the wider community. Building Cooperation Networks: Building cooperation between educational institutions, the media, the police, and the community to create a mutual awareness program. Keywords =: Trafficking Drugs, Mother and Child, Authorities, Public Awareness